REDESAIN BANGUNAN GEDUNG RUMAH SAKIT ROYAL SURABAYA MENURUT PERMENKES NOMOR 24 TAHUN 2016 - Raka Irawan, Adi Lintang (Universitas Negeri Surabaya, 2023)
Surabaya is the capital city of East Java, which has various types of public and private hospitals. One of the private hospitals in East Surabaya is the Royal Surabaya Hospital. Royal Surabaya Hospital is a Class C private hospital that provides facilities and infrastructure in the health sector to advance public welfare and health. However, in the Royal Surabaya Hospital building, there are discrepancies in PERMENKES No. 24 of 2016, among others: some room areas that are not suitable and room zoning that is less uniform. Therefore, this research was conducted to redesign the Royal Surabaya Hospital building based on PERMENKES Number 24 of 2016. The method carried out in this study uses data collection methods in the form of observation, work drawings, and literature methods. The results of this study are in the form of space redesign at the Royal Hospital in the form of zoning groupings which are divided into 3 zones (public, semi-private, and private zoning), changes occurred in building A including the Obstetrics room which was previously on the 1st floor moving to the 2nd floor, the Operating Room and ICU which was previously on the 3rd floor changing to the 2nd floor, Hemodialysis and endoscopy rooms which were originally on the 3rd floor moved to the 1st floor, several class 1, 2, 3 inpatient rooms moved to the 3rd floor which were previously on the 2nd floor, the addition of disability toilets and the mortuary, as well as changes in room area that have referred to PERMENKES Number 24 of 2016 concerning technical requirements for hospital buildings and infrastructure.